This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: A LGORITHMS — S AMPLE S OLUTIONS Sample Problems I 1 Formulae you should know You should remember these properties from previous calculus classes: • log a ( b · c ) = log a ( b ) + log a ( c ) , • log a ( b/c ) = log a ( b ) log a ( c ) , • log a ( b c ) = c · log a ( b ) , • c log a ( b ) = b log a ( c ) , • 1 + x + x 2 + ··· + x n = x n +1 1 x 1 . 2 Sample Problems 2.1 Summation Problem 1: Let S k n be the sum 1 k + 2 k + 3 k + ··· + n k . Then 1. Calculate S 1 n and S 2 n , and 2. Show that S k n = O ( n k +1 ) . Proof: 1. We recall the formulas ( x + 1) 2 = x 2 + 2 x + 1 and ( x + 1) 3 = x 3 + 3 x 2 + 3 x + 1 . Then S 2 n = 1 2 + 2 2 + 3 2 + ··· + n 2 = 1 + (1 + 1) 2 + (2 + 1) 2 + ··· + (( n 1) + 1) 2 = 1 + (1 2 + 2 · 1 + 1) + (2 2 + 2 · 2 + 1) + ··· + (( n 1) 2 + 2( n 1) + 1) = (1 2 + 2 2 + ··· + ( n 1) 2 ) + 2(1 + 2 + ··· + ( n 1)) + n = ( S 2 n n 2 ) + 2( S 1 n n ) + n = S 2 n + 2 S 1 n n ( n + 1) . Simplifying by S 2 n , one gets S 1 n = n ( n +1) 2 . 1 Similarly, S 3 n = 1 3 + 2 3 + 3 3 + ··· + n 3 = 1 + (1 + 1) 3 + (2 + 1) 3 + ··· + (( n 1) + 1) 3 = 1 + (1 3 + 3 · 1 2 + 3 · 1 + 1) + (2 3 + 3 · 2 2 + 3 · 2 + 1)+ ··· + (( n 1) 3 + 3( n 1) 2 + 3( n 1) + 1) = (1 3 + 2 3 + ··· + ( n 1) 3 ) + 3(1 2 + 2 2 + ··· + ( n 1) 2 )+ +3(1 + 2 + ··· + ( n 1)) + n = ( S 3 n n 3 ) + 3( S 2 n n 2 ) + 3 S 1 n 1 + n = S 2 n + 3 S 2 n n 3 3 n 2 + n + 3 · n ( n 1) 2 = S 2 n + 3 S 2 n n (2( n 2 +3 n 1) 3( n 1)) 2 = S 2 n + 3 S 2 n n (2 n 2 +3 n +1) 2 = S 2 n + 3 S 2 n n ( n +1)(2 n +1) 2 . Simplifying by S 3 n , one gets S 2 n = n ( n +1)(2 n +1) 6 . 2. We recall that ( n + 1) k +1 = n k +1 + ( k + 1) n k + P k 1 ( n ) , where P k 1 is a polynomial of degree k 1 . Then S k +1 n = 1 k +1 + 2 k +1 + 3 k +1 + ··· + n k +1 = 1 + (1 + 1) k +1 + (2 + 1) k +1 + ··· + (( n 1) + 1) k +1 = 1 + (1 k +1 + ( k + 1) · 1 k + P k 1 (1)) + (2 k +1 + ( k + 1) · 2 k + P k 1 (2))+ ··· + (( n 1) k +1 + ( k + 1) · ( n 1) k + P k 1 ( n 1)) = (1 k +1 + 2 k +1 + ··· + ( n 1) k +1 ) + ( k + 1)(1 k + 2 k + ··· + ( n 1) k )+ +(1 + P k 1 (1) + P k 1 (2) + ··· + P k 1 ( n 1)) = ( S k +1 n n k +1 ) + ( k + 1)( S k n n k ) + O ( n k ) = S k +1 n + ( k + 1) S k n n k +1 + O ( n k ) Simplifying S k n , one gets S k n = n k +1 k +1 O ( n k ) , that is, S k n = O ( n k +1 ) . Problem 2: Calculate the sums n X k =0 k 2 k and n X k =0 k 2 2 k . Proof: Recall that n X k =0 x k = x n +1 1 x 1 . By differentiation, one obtains: n X k =0 kx k 1 = ( n + 1) x n ( x 1) x n +1 + 1 ( x 1) 2 = nx n +1 ( n + 1) x n + 1 ( x 1) 2 . Multiplying by x , one gets: n X k =0 kx k = nx n +2 ( n + 1) x n +1 + x ( x 1) 2 , ( * ) and replacing x by 2, n X k =0 k 2 k = ( n 1)2 n +1 + 2 ....
View
Full
Document
This note was uploaded on 03/16/2010 for the course CSE 101 taught by Professor Staff during the Winter '08 term at UCSD.
 Winter '08
 staff

Click to edit the document details